Ein Kapitel nordindischer Religionspolitik im 18. Jahrhundert: Jai Singh II. und die religiösen Orden - Horstmann, Monika (Zeitschrift für Religionswissenschaft, 1994)
The reign of Mahārāja Jai Singh II (r. 1700-1743) is contemporaneous with the gradual decline of the imperial power of the Mughals. They were the suzerains of his dynasty, the Kachavähä family, and ever since the latter part of the 16th century the Kachavähäs had been allied with the Mughal court. So was Jai Singh. However, the reign of this Mughal ally is also characterised by a visible and articulate definition of his rulership as a Hindu one, notwithstanding the fact that his court and its courtly culture are informed by the Mughal Court. Jai Singh's territory is conceived as a Hindu cosmos, which is visibly expressed in the architecture and organisation of the residence which he built for himself, Jaipur. Within this Hindu territory Jai Singh also organised the religious life and the conduct of religious groups. Due to his influence over much wider regions of North India, this affected those parts, too. Jai Singh's measures met requirements which overlapped: One was the prince's religious and theological commitment, personally and officially in relation with his idea of Hindu kingship; another was the need to pacify an ongoing tension among religious groups over rank, influence and resources, while a third requirement emerged from the growing militancy of religious groups who thus came to form a power factor potentially at conflict with the state. This paper tries to analyse some of the various motives of Jai Singh's religious-political moves with the focus on his policy affecting the militant orders of Vaisnava or related sectarian affiliation.